1995
DOI: 10.1111/j.2042-7158.1995.tb05754.x
|View full text |Cite
|
Sign up to set email alerts
|

857-860Anti-inflammatory Effect of Magnolol, Isolated fromMagnolia officinalis, on A23187-induced Pleurisy in Mice

Abstract: In the present study, A23187‐induced pleurisy in mice was used to investigate the anti‐inflammatory effect of magnolol, a phenolic compound isolated from Chinese medicine Hou p'u (cortex of Magnolia officinalis). A23187‐induced protein leakage was reduced by magnolol (10mgkg−1, i.p.), indomethacin (10mgkg−1, i.p.) and BW755C (30mgkg−1, i.p.). A23187‐induced polymorphonuclear (PMN) leucocyte infiltration in the pleural cavity was suppressed by magnolol and BW755C, while enhanced by indomethacin. Like BW755C, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…The oriental anti-inflammatory herb [109], Magnolia officinalis, has long been used in East Asian countries. Its magnolol and honokiol potently inhibit P. acnes and P. granulosum (MIC = 3-4 and 9 lg ml , respectively) with the proven anti-inflammatory effects [110].…”
Section: Subjectively Used Herbsmentioning
confidence: 99%
“…The oriental anti-inflammatory herb [109], Magnolia officinalis, has long been used in East Asian countries. Its magnolol and honokiol potently inhibit P. acnes and P. granulosum (MIC = 3-4 and 9 lg ml , respectively) with the proven anti-inflammatory effects [110].…”
Section: Subjectively Used Herbsmentioning
confidence: 99%
“…This compound has been demonstrated to possess various pharmacological activities, such as anticancer, antibacterial, antioxidative, and anti-inflammatory activities (Wang et al, 1995;Park et al, 2004;Chen et al, 2009;Lee et al, 2009 supercritical carbon dioxide extract (MBSE, containing at least 93% magnolol) is now used as a food supplement in mints and gums to freshen breath (Greenberg et al, 2007). It was presumed that the application of this compound was very safe and had many beneficial effects .…”
Section: Introductionmentioning
confidence: 99%
“…Hesperidin, as the main compound of Fructus Aurantii, stimulated the gastrointestinal movement (Fang et al, 2009), exhibited antinociceptive activities in the abdominal writhing and hot-plate test (Loscalzo et al, 2011) and showed antiinflammatory properties (Manthey et al, 2001). Naringenin, magnolol and muscone showed anti-inflammatory effects (Hsu et al, 2004;Liang et al, 2010;Park et al, 2004;Tsai et al, 1999;Wang et al, 1995). Anthraquinone derivatives including aloe-emodin, rhein and sennosides also showed anti-inflammatory effects (Ma et al, 2009).…”
Section: Discussionmentioning
confidence: 99%